Equal justice : a biography of Sandra Day O'Connor - Woods, Harold; Woods, Geraldine (Minneapolis, Minn. : Dillon Press, 1985)
A biography of Sandra Day O'Connor, the first woman Supreme Court justice, which includes her childhood, her early legal career, and her life since her appointment.
Includes index.
Bibliography: p. [123]-124.
Keywords: O'Connor, Sandra Day, -- 1930- -- Juvenile literature; O'Connor, Sandra Day, -- 1930-; United States. -- Supreme Court -- Biography; Judges -- United States -- Biography -- Juvenile literature; Judges; Women -- Biography